A REVIEW OF FOULING OF RO MEMBRANES: FORMATION - Agam Muarif; Rizka Mulyawan (Universitas 17 Agustus 1945 (UNTAG) Semarang, 2022)
Membrane application in reverse osmosis (RO) membrane is getting more attention especially in producing drinking water. However, RO membrane faces challenges that reduces its performance such as its permeation flux, salt rejection, additional energy demand, lifetime decrease, extra pre-treatment process, cleaning and maintenance. The challenge is the formation of fouling. RO membrane fouling can happen inside or outside the membrane and the characteristics of membrane fouling differs from one type to other types, depending on the nature and location of membrane fouling. There are several types of RO fouling, which are Biofouling, Organic Fouling, Inorganic Fouling and Colloidal Fouling. The causes of RO membrane are different from one to another. The properties and materials of the solution entering RO membrane are important as it affects the type of fouling of RO membrane fouling. All of the RO membrane foulings need to be considered during membrane usage and demand solution to be controlled.